Biochemical Properties and Multifunctional Applications of Galactomannan Derived From Trigonella Foenum-Graecum - V.Ragul; A.Priyadharshini; S.Manoranjit; A.Jagadeesa; S. Raman; S.Chandru (Asian Journal of Pharmaceutical Research and Development, 2025)
Galactomannan is an important biological and functional ingredient of fenugreek (Trigonella foenum-graecum) seeds. It is the primary storage polysaccharide in the endosperm, providing a significant source of energy for germination and early seedling development. Fenugreek galactomannan, which is structurally made of a mannose backbone with galactose side chains, is distinguished by its comparatively high galactose-to-mannose ratio, which boosts its solubility in water and aids the production of a smooth, viscous mucilage when the seeds are hydrated. This mucilage helps the seed retain moisture, protects it from dehydration, and acts as a physical barrier to mechanical harm, making it critical for seed survival in natural environments. Galactomannan is appreciated in human nutrition as a soluble dietary fiber with a variety of health benefits. Its capacity to increase intestinal viscosity slows carbohydrate digestion and absorption, hence regulating postprandial blood glucose levels. By delaying stomach emptying, it enhances fullness, which may aid in appetite control and weight management. Furthermore, galactomannan can bind bile acids and limit cholesterol absorption, resulting in better lipid profiles. Because of its physiological benefits, fenugreek galactomannan is a popular ingredient in nutraceutical formulations that promote metabolic and cardiovascular health. Because of its good rheological qualities, fenugreek galactomannan is used in the industrial sector as a natural thickener, stabilizer, and emulsifier. Its high solubility and ability to form uniform gels make it helpful in foods, beverages, and pharmaceutical preparations, including controlled-release drug delivery systems. Overall, galactomannan is essential to both the biological activity of fenugreek seeds and the variety of nutritional and industrial applications associated with them.